ANALISIS LOST CIRCULATION PEMOMPAAN GRAVEL SLURRY PADA SUMUR X BERDASARKAN WAKTU TUNGGU - Novrianti Novrianti; Ali Musnal; Febriyan Ramadhan (Jurusan Teknik Perminyakan Fakultas Teknologi Kebumian dan Energi Universitas Trisakti, 2016)
Unconsolidated formations tend to have sand problem that can lead to decline of production in Oil and Gas Well. There are some methods can be used to resolve sand problem like liner completion, meshrite liner, perforated liner completion, and gravel pack completion. Rock type of Well X is unconsolidated stone and the method which used in that well to surmount sand problem that occurred is gravel pack method. However, during pumping of gravel slurry there are some problems, partial or complete loss of the gravel slurry into the formation (lost circulation), waiting on sand sattle is one method that has developed to resolve loss circulation. This method is done by stopping pumping slurry after the amount of incoming sand has reached teoritical and more than 50%. The aim of this research to determine volume of gravel slurry that is needed and total of lost gravel sand. Gravel slurry needed to overcome sand problem in Well X consists of 109 sacks of gravel sand, 259.5 bbl of water, and 1834 lb (18 sacks) of KCL. Analysis of pressure test line chart to find out lost circulation problem. There are 147 sacks gravel sand missing as a result of lost circulation problem from 256 sacks of gravel sand that is pumped.